Strategies for Successful Blended Learning—A Bibliometric Analysis and Reviews - Hassan Abuhassna; Nguyen Thuy Van; Noraffandy Yahaya; Megat Aman Zahiri Megat Zakaria; Fareed Awae; Diaya Ud Deen Al Zitawi; Kawthar Bayoumi, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Recently, the term blended learning (BL) emerged as a new trend in teaching models and learning styles with the digital advantages support. This article presents a systematic review of literature that explores the strategies for successful BL in multi-sides to enhance student learning and development outcomes. To reach the objectives, the literature accessed of Scopus and web of science databases covering research published between 2011 and 2021 and 39 items were analysed. The bibliometric analysis identifies the cluster themes based on texting frequency. The vital steps of data classification follow thoughtfully and carefully in the platform of concept, findings, author's reputation, and years published. In the last conclusions of the study, reports explain the past literature and recent outbreak. The results cover three main themes: digital support for student engagement, personalisation learning, and instructors of management courses. These findings are expected to benefit stakeholders involved in employing BLin which instructors use integrated technology and online learning materials with traditional face-to-face classroom activities.